2021
DOI: 10.1371/journal.pgen.1009485
|View full text |Cite
|
Sign up to set email alerts
|

Sperm acrosome overgrowth and infertility in mice lacking chromosome 18 pachytene piRNA

Abstract: piRNAs are small non-coding RNAs required to maintain genome integrity and preserve RNA homeostasis during male gametogenesis. In murine adult testes, the highest levels of piRNAs are present in the pachytene stage of meiosis, but their mode of action and function remain incompletely understood. We previously reported that BTBD18 binds to 50 pachytene piRNA-producing loci. Here we show that spermatozoa in gene-edited mice lacking a BTBD18 targeted pachytene piRNA cluster on Chr18 have severe sperm head dysmorp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 72 publications
8
45
0
Order By: Relevance
“…[40][41][42][44][45][46] and reach a peak abundance in spermatocytes rivalling that of ribosomes 16 . Pachytene piRNAs tune the abundance of mRNAs required for spermiogenesis, the process by which round spermatids become sperm [47][48][49][50] . Pachytene piRNAs have been proposed to direct MIWI and MILI to cleave specific mRNAs, ensuring appropriate levels of their protein products 47,[50][51][52] .…”
Section: Mainmentioning
confidence: 99%
“…[40][41][42][44][45][46] and reach a peak abundance in spermatocytes rivalling that of ribosomes 16 . Pachytene piRNAs tune the abundance of mRNAs required for spermiogenesis, the process by which round spermatids become sperm [47][48][49][50] . Pachytene piRNAs have been proposed to direct MIWI and MILI to cleave specific mRNAs, ensuring appropriate levels of their protein products 47,[50][51][52] .…”
Section: Mainmentioning
confidence: 99%
“…Notable exceptions are the mouse pachytene piRNAs, which are derived from so-called 'pachytene piRNA clusters' that are expressed during spermatogenesis at the pachytene stage of meiosis 1,2,6,7 . Pachytene piRNA clusters show no enrichment of transposon-complementary sequences but may regulate some protein-coding genes [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Defective capacitation and failure to bind and penetrate the zona pellucida have been reported in pachytene piRNA mutant sperm (Wu et al, 2020). Choi et al found sperm acrosome growth and infertility in mice lacking chromosome 18 pachytene piRNA (Choi et al, 2021). In light of the significant regulatory role of ERK1/2 in boar sperm capacitation (Awda and Buhr, 2010), piR-121380 might have an indirect role in regulating acrosomal reaction through ERK2 phosphorylation in mature boar sperm.…”
Section: Discussionmentioning
confidence: 99%